2019
DOI: 10.1021/acs.orglett.9b03317
|View full text |Cite|
|
Sign up to set email alerts
|

Photoinduced Hydroxylation of Organic Halides under Mild Conditions

Abstract: Presented in this paper is photoinduced hydroxylation of organic halides, providing a mild access to a range of functionalized phenols and aliphatic alcohols. These reactions generally proceed under mild reaction conditions with no need for a photocatalyst or a strong base and show a wide substrate scope as well as excellent functional group tolerance. This work highlights the unique role of NaI that allows a challenging transformation to proceed under mild reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
(18 reference statements)
0
9
0
Order By: Relevance
“…Arene hydroxylation reactions are powerful enabling synthetic methods which are routinely used in the preparation of high-value pharmaceuticals, agrochemicals, polymers and natural products. 1 Many different synthetic approaches have been developed to form aryl C(sp 2 )–OH bonds, 2 but in terms of cost, operational simplicity and toxicity, nucleophilic aromatic substitution (S N Ar) 3 represents one of the most attractive and frequently used methods. 4 However, the broad application and selectivity of this approach is limited by the high basicity and low nucleophilicity of the hydroxide anion.…”
Section: Introductionmentioning
confidence: 99%
“…Arene hydroxylation reactions are powerful enabling synthetic methods which are routinely used in the preparation of high-value pharmaceuticals, agrochemicals, polymers and natural products. 1 Many different synthetic approaches have been developed to form aryl C(sp 2 )–OH bonds, 2 but in terms of cost, operational simplicity and toxicity, nucleophilic aromatic substitution (S N Ar) 3 represents one of the most attractive and frequently used methods. 4 However, the broad application and selectivity of this approach is limited by the high basicity and low nucleophilicity of the hydroxide anion.…”
Section: Introductionmentioning
confidence: 99%
“…The study indicated that the reaction does not involve any possible hydrogen peroxide radicals, such as hydroxyl radical, peroxy hydroxyl radical, and superoxide radical [34] . A plausible mechanism for the reaction has been proposed based on the previously reported literature [32] . The transformation of boronic acid II to phenol V was accelerated rapidly by forming boronic acid adduct III with activated hydrogen peroxide complex I , which further undergoes rearrangement to give intermediate compound IV and final hydrolysis yielded phenol V (see Supporting information, Figure S1) [34] …”
Section: Figurementioning
confidence: 82%
“…Earlier reported protocol for the synthesis of benzofuranone ( 9 u ) utilizes a stoichiometric amount of catalyst, required elevated temperature, and resulted in a relatively lower yield (Figure 2B) [30] . The synthesis of a protein disulfide isomerase inhibitor derivative of menthol ( 2 aa ) was accomplished in 86 % yield by using the developed protocol, whereas the previously developed protocol utilized UV light irradiation over 24 h in the presence of molecular O 2 and provided comparatively lower yield (69 %) of the desired product (Figure 2C) [31,32] …”
Section: Figurementioning
confidence: 96%
“…The synthetic routes of 4‐[4‐(9 H ‐carbazol‐9‐yl)phenoxy]phthalonitrile (P‐CN), 3‐[4‐(9 H ‐carbazol‐9‐yl)phenoxy]phthalonitrile (N‐CN) and metallophthalocyanines (PCo, PMn, NCo, and NMn) have been shown in Figure 1. 4‐[4‐(9 H ‐Carbazol‐9‐yl)phenoxy]phthalonitrile, 3‐[4‐(9 H ‐carbazol‐9‐yl)phenoxy]phthalonitrile were prepared by the reaction between 4‐(9 H ‐carbazol‐9‐yl)phenol [ 38 ] 1 and 4‐nitrophthalonitrile, 3‐nitrophthalonitrile. Then, peripheral or nonperipheral tetra‐[4‐(9 H ‐carbazol‐9‐yl)phenoxy] substituted cobalt(II), manganese(III) phthalocyanines (PCo, PMn, NCo, and NMn) were synthesized by a cyclotetramerization reaction of the 4‐[4‐(9 H ‐carbazol‐9‐yl)phenoxy]phthalonitrile (P‐CN), 3‐[4‐(9 H ‐carbazol‐9‐yl)phenoxy]phthalonitrile (N‐CN).…”
Section: Resultsmentioning
confidence: 99%